High-safety semi-solid lithium ion battery diaphragm and preparation method thereof

Through wet asynchronous stretching process and crystal plating liquid spraying technology, a semi-solid lithium-ion battery separator with high safety and high mechanical strength was prepared, which solved the problems of insufficient mechanical strength of the separator and difficulty in suppressing lithium dendrites in the existing technology, and achieved stable improvement of electrochemical performance and guaranteed high temperature safety.

CN119674431APending Publication Date: 2025-03-21SINOMA LITHIUM BATTERY SEPARATOR CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411917976.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to design a semi-solid lithium-ion battery separator with high safety, high mechanical strength and stable electrochemical performance, especially in terms of safety issues in lithium dendrites suppression and high temperature environments.

Method used

A semi-solid lithium-ion battery separator is prepared by wet asynchronous stretching process. By spraying crystal plating liquid on the surface of the film and performing multi-directional simultaneous oriented tensiles, the mechanical strength and anti-oxidation properties of the film are enhanced.

Benefits of technology

It significantly improves the mechanical strength and electrochemical properties of the lithium-ion battery separator, can maintain good safety in high temperature environments, and effectively inhibit the growth of lithium dendrites.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-safety semi-solid lithium ion battery diaphragm and a preparation method thereof, and belongs to the technical field of preparation of semi-solid lithium ion battery diaphragms. The preparation method of the high-safety semi-solid lithium ion battery diaphragm comprises the following steps: step 1, firstly feeding, namely pre-treating raw materials such as PE (Polyethylene) and a pore-forming agent according to a formula, and conveying the pre-treated raw materials to an extrusion system; in order to solve the problems that polyethylene glycol and graphene are used as main manufacturing raw materials of a battery diaphragm, although polyethylene glycol and graphene have the advantages of high temperature resistance and high ionic conductivity, the mechanical strength of a thin film is poor, and when the thin film is used in a semi-solid lithium ion battery, the service life of the battery diaphragm is prolonged. In order to solve the problem that the existing battery diaphragm is likely to be scratched by a solid composition in a battery, in the wet preparation process of the battery diaphragm, multi-direction oriented stretching is adopted, and multi-direction stretching work is carried out at the same time to ensure that micropores in the stretched film are uniformly distributed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semi-solid lithium-ion battery diaphragm preparation, in particular to a highly safe semi-solid lithium-ion battery diaphragm and a preparation method thereof. Background Art

[0002] In the structure of lithium batteries, the diaphragm is one of the key internal components of lithium batteries. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle and safety performance. The diaphragm with excellent performance plays an important role in improving the comprehensive performance of the battery. The main function of the diaphragm is to separate the cathode and anode (positive and negative) materials of the battery to prevent short circuits between the two levels of contact. In addition, during the electrochemical reaction, it can maintain the necessary electrolyte and form a channel for ion movement. The low energy density and safety issues of liquid lithium-ion batteries can no longer meet the growing demand for large-scale energy storage systems. As a low-cost alternative, solid-state lithium metal batteries show great competitive advantages and broad application prospects due to their high energy density and good safety. However, solid-state electrolyte composite diaphragms often have low ionic conductivity, and the poor interfacial compatibility and poor stability between solid-state electrolyte composite diaphragms and electrodes will lead to continuous deterioration of electrochemical performance. At present, solid-state electrolyte composite diaphragms, which are usually prepared with inorganic ceramic materials and organic polymers, cannot efficiently achieve lithium ion conduction and inhibition of lithium dendrites. How to design ultra-thin electrolyte separators for composite semi-solid lithium-ion batteries remains a challenge;

[0003] In the electrolyte phase of the battery cell, half of the mass or volume is solid electrolyte and the other half is liquid electrolyte; or one end of the electrode in the battery cell is all solid and the other end contains liquid;

[0004] National patent application publication number: CN114944537A Patent name: Preparation method of graphene-polyethylene glycol-based polymer conversion membrane, the liquid solution of polyethylene glycol-based polymer, cyclodextrin group molecule, and end-capping polymer is mixed, and doped graphene additives are added, and the resulting mixed solution is cast into a membrane, and then ultrasonically treated and vacuum dried in the conversion liquid to obtain a porous polymer and soaked and ultrasonically treated in an electrolyte containing lithium salt or sodium salt to obtain a doped graphene-polyethylene glycol-based polymer conversion membrane. The present invention can significantly improve the liquid absorption and retention capacity, high temperature resistance, ionic conductivity, surface impedance and battery compatibility of the polymer, and only involves enhancing the liquid absorption and retention capacity, high temperature resistance, ionic conductivity, surface impedance and battery compatibility of the battery separator, but does not mention the aspect of enhancing the mechanical strength of the battery separator;

[0005] Most microporous membranes are made of polyethylene (PE), polypropylene (PP) and composite membranes of these two membranes such as PE / PP and PP / PE / PP, etc., while the ideal electrolyte separator should have a porous structure, high liquid absorption rate, strong mechanical strength, thin thickness, stable electrochemical performance, and can prevent the growth of lithium dendrites. In addition, for the safety of the battery, it can block the battery at high temperature. Summary of the invention

[0006] The object of the present invention is to provide a highly safe semi-solid lithium-ion battery separator and a preparation method thereof. The battery separator is prepared by a wet asynchronous stretching process, while the traditional wet asynchronous stretching process is to orient and stretch the battery separator in the horizontal and vertical directions in sequence. The micropore distribution on the stretched film is not uniform enough, and there are relatively coarse film fibers that have not been stretched. Therefore, the stretching of the battery separator can be changed to simultaneously perform directional stretching in the horizontal and vertical directions. Moreover, before the extraction process of the battery separator (the base film is extracted with a solvent to form a base film without a pore-forming agent), a crystal plating liquid can be sprayed on the surface of the film when the film is oriented and stretched in multiple directions at the same time. The crystal plating liquid can adhere to the surface of the film, and the crystal plating liquid solidifies on the outer surface of the film to form an extremely thin plating surface, which not only enhances the mechanical strength of the film (prevents the battery separator from being scratched by the solid components in the semi-solid lithium-ion battery), but also enhances the anti-oxidation properties of the film, which can solve the problems in the prior art.

[0007] To achieve the above object, the present invention provides the following technical solution: a highly safe semi-solid lithium-ion battery separator, characterized in that the semi-solid lithium-ion battery separator is made of polyethylene oxide as a main material, lithium aluminum titanium phosphate, aramid, N-dimethyl pancreatic amine and aramid cosolvent in proportion, heated, mixed and pressed;

[0008] The specification of the polyethylene oxide is Mw: 1000000;

[0009] The solid content of the aramid fiber is 21.5%;

[0010] A method for preparing a highly safe semi-solid lithium-ion battery separator comprises the following steps:

[0011] Step 1: First, polyethylene oxide is used as the main material, and lithium aluminum titanium phosphate, aramid, N-dimethyl pancreatic amine and aramid cosolvent are mixed and heated in proportion for pretreatment and transported to the extrusion system. The solid electrolyte solution is poured into the extrusion system, and then the solvent is evaporated to obtain a solid electrolyte membrane. The solid electrolyte membrane is heated and extruded again through the extrusion system to become a melt, and the thickness of the membrane is controlled by adjusting the volume and concentration of the solution.

[0012] Step 2: The melt after heating and extrusion by the extrusion system is poured into the mold, and the melt is cast to form a cast thick sheet containing a pore-forming agent;

[0013] Step 3: Spray the solution used for coating the thin film onto the cast thick sheet through a spray gun;

[0014] Step 4: Then connect the cast thick sheet to the stretching devices placed in multiple directions around it, and then start multi-directional simultaneous orientation stretching. During the stretching process, the extension speed of the cast thick sheet must be kept uniform;

[0015] Step 5: extracting the base film with a solvent to form a base film without a pore-forming agent (using deionized water, an organic solvent and a surfactant to prepare a cleaning solution, and the ratio of deionized water, organic solvent and surfactant is 1:1:1.2);

[0016] Step six: In the step three, polysiloxane, polysilazane and inorganic silicon in a ratio of 1:0.5:1.2 are mixed into water, and the ratio of the polysiloxane, polysilazane and inorganic silicon mixture to water is 1:8. The mixed solution is stirred with water and then sprayed on the cast thick sheet through a spray gun.

[0017] Preferably, in step four, the stretching device performs multi-directional orientation stretching on the thick cast film whose surface has been sprayed with the crystal plating solution, and the solidified crystal plating layer on the surface of the thick cast film is broken into individual fragments distributed on the diaphragm after stretching, which will not block the normal exchange of electrolyte in the micropores on the film.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The mechanical strength of the lithium-ion battery diaphragm sprayed with polysiloxane, polysilazane and inorganic silicon solution of the present invention is >1000kg cm-1, while the mechanical strength of the lithium-ion battery diaphragm sprayed with polysiloxane, polysilazane and inorganic silicon solution is far from reaching this ideal standard, because the crystal plating mixed solution is sprayed on the lithium-ion battery diaphragm and then stretched, and the crystal plating mixed solution will adhere to the skeleton, which is equivalent to increasing the thickness of the skeleton: this solution not only does not affect the normal electrolyte exchange of the micropores on the lithium-ion battery diaphragm, but also has good mechanical strength.

[0020] 2. The present invention adopts a wet process to prepare lithium-ion battery separators, which is commonly used in the preparation of inorganic electrolyte membranes and composite electrolyte membranes. The solid electrolyte solution is directly poured on the surface of the positive electrode. After the solvent is evaporated, a solid electrolyte membrane is formed on the surface of the positive electrode. Compared with mold support, positive electrode support can obtain a thinner solid electrolyte membrane and better interface contact. Wang et al. prepared the positive electrode sheet by casting, and after removing the solvent, the electrolyte slurry was cast onto the positive electrode sheet to form a solid electrolyte membrane supported by the positive electrode. Active materials and other additives accumulate inside the positive electrode to form a large number of pores.

[0021] 3. The skeleton support process used in the present invention is commonly used in the preparation of composite electrolyte membranes. The solid electrolyte solution is injected into the skeleton, and after the solvent is evaporated, a solid electrolyte membrane with skeleton support is formed. The active skeleton made by the present invention. The PI membrane is non-flammable and has high mechanical strength. The vertical channels provided can enhance the ionic conductivity of the polymer electrolyte (2.3x104S / cm at 30°C). The all-solid-state lithium-ion battery made of PIPEO / LITESI solid electrolyte membrane shows good cycle performance at a temperature of 60°C (200 cycles at C / 2 rate), and can withstand abuse tests such as bending, shearing and puncture. DETAILED DESCRIPTION

[0022] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0023] In order to solve the problem that the dissolved water-soluble lithium is adsorbed by the hydrated silicate colloid and cannot be separated, and the lithium and aluminum form lithium-aluminum co-precipitation slag in the deep impurity removal and purification stage, and it is difficult to separate them; this embodiment provides the following technical solutions:

[0024] A highly safe semi-solid lithium-ion battery separator and a preparation method thereof, comprising the following steps:

[0025] 1) First, polyethylene oxide is used as the main material, and lithium aluminum titanium phosphate, aramid, N-dimethyl pancreatic amine and aramid cosolvent are heated and mixed in proportion for pretreatment and transported to the extrusion system. The solid electrolyte solution is poured into the extrusion system, and then the solvent is evaporated to obtain a solid electrolyte membrane. The solid electrolyte membrane is heated and extruded again by the extrusion system to become a melt, and the thickness of the membrane is controlled by adjusting the volume and concentration of the solution.

[0026] 2) The melt after heating and extrusion by the extrusion system is poured into the mold, and the melt is cast to form a cast thick sheet containing a pore-forming agent;

[0027] 3) Spraying the solution used for coating the thin film onto the cast thick sheet through a spray gun;

[0028] 4) Then, the thick film is connected to the stretching devices placed in multiple directions around it, and then the multi-directional simultaneous orientation stretching is started. During the stretching process, the extension speed of the thick film must be kept uniform;

[0029] 5) extracting the base film with a solvent to form a base film without a pore-forming agent (using deionized water, an organic solvent and a surfactant to prepare a cleaning solution, and the ratio of deionized water, organic solvent and surfactant is 1:1:1.2);

[0030] 6) In the step 3, polysiloxane, polysilazane and inorganic silicon in a ratio of 1:0.5:1.2 are mixed into water, and the ratio of the polysiloxane, polysilazane and inorganic silicon mixture to water is 1:8, and the mixed solution is stirred with water and then sprayed on the cast thick sheet through a spray gun;

[0031] 7) The stretching device performs multi-directional orientation stretching on the cast thick film whose surface has been sprayed with the plating solution, and the solidified plating layer on the surface of the cast thick film is broken into pieces and distributed on the diaphragm after stretching, which will not block the normal exchange of electrolyte in the micropores on the film.

[0032] Embodiment 1:

[0033] Raw material preparation: Wash the PE material blocks of basically the same size and shape, and then put them into the heating device for heating and softening;

[0034] 1) First, polyethylene oxide is used as the main material, and lithium aluminum titanium phosphate, aramid, N-dimethyl pancreatic amine and aramid cosolvent are heated and mixed in proportion for pretreatment and transported to the extrusion system. The solid electrolyte solution is poured into the extrusion system, and then the solvent is evaporated to obtain a solid electrolyte membrane. The solid electrolyte membrane is heated and extruded again by the extrusion system to become a melt, and the thickness of the membrane is controlled by adjusting the volume and concentration of the solution.

[0035] 2) The melt after heating and extrusion by the extrusion system is poured into the mold, and the melt is cast to form a cast thick sheet containing a pore-forming agent;

[0036] 3) Spraying the solution used for coating the thin film onto the cast thick sheet through a spray gun;

[0037] 4) Then, the thick film is connected to the stretching devices placed in multiple directions around it, and then the multi-directional simultaneous orientation stretching is started. During the stretching process, the extension speed of the thick film must be kept uniform;

[0038] 5) extracting the base film with a solvent to form a base film without a pore-forming agent (using deionized water, an organic solvent and a surfactant to prepare a cleaning solution, and the ratio of deionized water, organic solvent and surfactant is 1:1:1.2);

[0039] 6) In the step 3, polysiloxane, polysilazane and inorganic silicon in a ratio of 1:0.5:1.2 are mixed into water, and the ratio of the polysiloxane, polysilazane and inorganic silicon mixture to water is 1:8, and the mixed solution is stirred with water and then sprayed on the cast thick sheet through a spray gun;

[0040] 7) The stretching device performs multi-directional orientation stretching on the cast thick film whose surface has been sprayed with the plating solution, and the solidified plating layer on the surface of the cast thick film is broken into pieces and distributed on the diaphragm after stretching, which will not block the normal exchange of electrolyte in the micropores on the film.

[0041] Observation of film micropores: Polysiloxane, polysilazane and inorganic silicon were mixed into water at a ratio of 1:0.5:1.2, and the ratio of the mixture of polysiloxane, polysilazane and inorganic silicon to water was 1:8. After stretching, a layer of 10μm thick plated crystal fragment film would adhere to the walls between the micropores of the film, and the mechanical properties of the film at this time were >1000kg cm-1 (98.06MPa).

[0042] Embodiment 2:

[0043] Raw material preparation: Wash the PE material blocks of basically the same size and shape, and then put them into the heating device for heating and softening;

[0044] 1) First, polyethylene oxide is used as the main material, and lithium aluminum titanium phosphate, aramid, N-dimethyl pancreatic amine and aramid cosolvent are heated and mixed in proportion for pretreatment and transported to the extrusion system. The solid electrolyte solution is poured into the extrusion system, and then the solvent is evaporated to obtain a solid electrolyte membrane. The solid electrolyte membrane is heated and extruded again by the extrusion system to become a melt, and the thickness of the membrane is controlled by adjusting the volume and concentration of the solution.

[0045] 2) The melt after heating and extrusion by the extrusion system is poured into the mold, and the melt is cast to form a cast thick sheet containing a pore-forming agent;

[0046] 3) Spraying the solution used for coating the thin film onto the cast thick sheet through a spray gun;

[0047] 4) Then, the thick film is connected to the stretching devices placed in multiple directions around it, and then the multi-directional simultaneous orientation stretching is started. During the stretching process, the extension speed of the thick film must be kept uniform;

[0048] 5) extracting the base film with a solvent to form a base film without a pore-forming agent (using deionized water, an organic solvent and a surfactant to prepare a cleaning solution, and the ratio of deionized water, organic solvent and surfactant is 1:1:1.2);

[0049] 6) In the step 3, polysiloxane, polysilazane and inorganic silicon in a ratio of 1:1:0.8 are mixed into water, and the ratio of the polysiloxane, polysilazane and inorganic silicon mixture to water is 1:8, and the mixed solution is stirred with water and then sprayed on the cast thick sheet through a spray gun;

[0050] 7) The stretching device performs multi-directional orientation stretching on the cast thick film whose surface has been sprayed with the plating solution, and the solidified plating layer on the surface of the cast thick film is broken into pieces and distributed on the diaphragm after stretching, which will not block the normal exchange of electrolyte in the micropores on the film.

[0051] Observation of film micropores: Polysiloxane, polysilazane and inorganic silicon were mixed into water at a ratio of 1:1:0.8, and the ratio of the mixture of polysiloxane, polysilazane and inorganic silicon to water was 1:8. After stretching, a layer of 7μm thick plated crystal fragment film would adhere to the walls between the micropores of the film, and the mechanical properties of the film at this time were >800kg cm-1 (98.06MPa).

[0052] Embodiment 3:

[0053] Raw material preparation: Wash the PE material blocks of basically the same size and shape, and then put them into the heating device for heating and softening;

[0054] 1) First, polyethylene oxide is used as the main material, and lithium aluminum titanium phosphate, aramid, N-dimethyl pancreatic amine and aramid cosolvent are heated and mixed in proportion for pretreatment and transported to the extrusion system. The solid electrolyte solution is poured into the extrusion system, and then the solvent is evaporated to obtain a solid electrolyte membrane. The solid electrolyte membrane is heated and extruded again by the extrusion system to become a melt, and the thickness of the membrane is controlled by adjusting the volume and concentration of the solution.

[0055] 2) The melt after heating and extrusion by the extrusion system is poured into the mold, and the melt is cast to form a cast thick sheet containing a pore-forming agent;

[0056] 3) Spraying the solution used for coating the thin film onto the cast thick sheet through a spray gun;

[0057] 4) Then, the thick film is connected to the stretching devices placed in multiple directions around it, and then the multi-directional simultaneous orientation stretching is started. During the stretching process, the extension speed of the thick film must be kept uniform;

[0058] 5) extracting the base film with a solvent to form a base film without a pore-forming agent (using deionized water, an organic solvent and a surfactant to prepare a cleaning solution, and the ratio of deionized water, organic solvent and surfactant is 1:1:1.2);

[0059] 6) In the step 3, polysiloxane, polysilazane and inorganic silicon in a ratio of 0.8:1:1.2 are mixed into water, and the ratio of the polysiloxane, polysilazane and inorganic silicon mixture to water is 1:8, and the mixed solution is stirred with water and then sprayed on the cast thick sheet through a spray gun;

[0060] 7) The stretching device performs multi-directional orientation stretching on the cast thick film whose surface has been sprayed with the plating solution, and the solidified plating layer on the surface of the cast thick film is broken into pieces and distributed on the diaphragm after stretching, which will not block the normal exchange of electrolyte in the micropores on the film.

[0061] Observation of film micropores: Polysiloxane, polysilazane and inorganic silicon were mixed in water at a ratio of 0.8:1:1.2, and the ratio of the mixture of polysiloxane, polysilazane and inorganic silicon to water was 1:8. After stretching, a layer of 13μm thick plated crystal fragment film would adhere to the walls between the micropores of the film, which had better wrapping properties. At this time, the mechanical properties of the film were >1100kg cm-1 (98.06MPa).

[0062] Embodiment 4:

[0063] Raw material preparation: Wash the PE material blocks of basically the same size and shape, and then put them into the heating device for heating and softening;

[0064] 1) First, polyethylene oxide is used as the main material, and lithium aluminum titanium phosphate, aramid, N-dimethyl pancreatic amine and aramid cosolvent are heated and mixed in proportion for pretreatment and transported to the extrusion system. The solid electrolyte solution is poured into the extrusion system, and then the solvent is evaporated to obtain a solid electrolyte membrane. The solid electrolyte membrane is heated and extruded again by the extrusion system to become a melt, and the thickness of the membrane is controlled by adjusting the volume and concentration of the solution.

[0065] 2) The melt after heating and extrusion by the extrusion system is poured into the mold, and the melt is cast to form a cast thick sheet containing a pore-forming agent;

[0066] 3) The LLTO precursor was mixed with polyvinyl alcohol and gelled by a crosslinker and an initiator to synthesize a 3D nanostructured LLTO hydrogel. The dried LLTO hydrogel was heat treated in air at 800°C for 2h to form a 3D skeleton, which was then embedded in a thick film. The results showed that the composite solid electrolyte prepared by this method effectively inhibited the agglomeration of the filler, and significantly improved the thermal stability and electrochemical stability of the composite electrolyte. At the same time, the 3D skeleton formed a continuous lithium ion channel, and the ionic conductivity was close to 10-4S / cm at room temperature;

[0067] 4) Spraying the solution used for coating the thin film onto the cast thick sheet through a spray gun;

[0068] 5) Then, the thick film is connected to the stretching devices placed in multiple directions around it, and then the multi-directional simultaneous orientation stretching is started. During the stretching process, the extension speed of the thick film must be kept uniform;

[0069] 6) extracting the base film by solvent to form a base film without a pore-forming agent (using deionized water, an organic solvent and a surfactant to prepare a cleaning solution, and the ratio of deionized water, organic solvent and surfactant is 1:1:1.2);

[0070] 7) In the step 3, polysiloxane, polysilazane and inorganic silicon in a ratio of 0.8:1:1.2 are mixed into water, and the ratio of the polysiloxane, polysilazane and inorganic silicon mixture to water is 1:8, and the mixed solution is stirred with water and then sprayed on the cast thick sheet through a spray gun;

[0071] 8) The stretching device performs multi-directional orientation stretching on the cast thick film whose surface has been sprayed with the plating solution, and the solidified plating layer on the surface of the cast thick film is broken into pieces and distributed on the diaphragm after stretching, which will not block the normal exchange of electrolyte in the micropores on the film.

[0072] Observation of film micropores: 0.8:1:1.2 of polysiloxane, polysilazane and inorganic silicon were mixed in water, and the ratio of polysiloxane, polysilazane, inorganic silicon mixture to water was 1:8. After stretching, a layer of 13μm thick plated crystal fragment film would adhere to the walls between the micropores of the film, which had better wrapping properties. At this time, the mechanical properties of the film were >1100kg cm-1 (98.06MPa), and the ionic conductivity of the lithium-ion battery separator using the inert skeleton embedding process was significantly improved.

[0073] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0074] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

Claims

1. A highly safe semi-solid lithium-ion battery separator, characterized in that: The semi-solid lithium-ion battery separator is made of polyethylene oxide as the main material, lithium aluminum titanium phosphate, aramid, N-dimethyl pancreatic amine and aramid cosolvent, which are heated, mixed and pressed in proportion. The specification of the polyethylene oxide is Mw: 1000000; The solid content of the aramid fiber is 21.5%.

2. A method for preparing a highly safe semi-solid lithium-ion battery separator, characterized in that: The steps include: Step 1: First, polyethylene oxide is used as the main material, and lithium aluminum titanium phosphate, aramid, N-dimethyl pancreatic amine and aramid cosolvent are mixed and heated in proportion for pretreatment and transported to the extrusion system, and the solid electrolyte solution is poured into the extrusion system, and then the solvent is evaporated to obtain a solid electrolyte membrane. The solid electrolyte membrane is heated and extruded again by the extrusion system to become a melt, and the thickness of the membrane is controlled by adjusting the volume and concentration of the solution; Step 2: The melt after heating and extrusion by the extrusion system is poured into the mold, and the melt is cast to form a cast thick sheet containing a pore-forming agent; Step 3: Spray the solution used to coat the thin film onto the cast thick sheet through a spray gun; Step 4: Connect the cast thick sheet to the stretching devices placed in multiple directions around it, and then start multi-directional simultaneous orientation stretching. During the stretching process, the extension speed of the cast thick sheet is kept uniform; Step 5: extracting the base film with a solvent to form a base film without a pore-forming agent, and preparing a cleaning solution using deionized water, an organic solvent and a surfactant, wherein the ratio of deionized water, the organic solvent and the surfactant is 1:1:1.2; Step six: drying and shaping the base film without pore-forming agent to obtain a lithium-ion battery separator.

3. The method for preparing a highly safe semi-solid lithium-ion battery separator according to claim 2, characterized in that: In step three, polysiloxane, polysilazane and inorganic silicon in a ratio of 1:0.5:1.2 are mixed into water, and the ratio of the polysiloxane, polysilazane and inorganic silicon mixture to water is 1:

8. The stirred and mixed solution is sprayed on the cast thick sheet through a spray gun.

4. The method for preparing a highly safe semi-solid lithium-ion battery separator according to claim 2, characterized in that: In step 4, the stretching device performs multi-directional orientation stretching on the thick cast film whose surface has been sprayed with the plating solution, and the solidified plating layer on the surface of the thick cast film is stretched into fragments and distributed on the diaphragm, which will not block the normal exchange of electrolyte in the micropores on the film.

5. The method for preparing a highly safe semi-solid lithium-ion battery separator according to claim 2, characterized in that: In step 5, deionized water refers to pure water from which ionized impurities have been removed. The definition of "deionized" specified by the International Organization for Standardization ISO / TC 147 is: "Deionized water is water from which ions have been completely or partially removed." 6. The method for preparing a highly safe semi-solid lithium-ion battery separator according to claim 2, characterized in that: In step 5, organic solvents are a large class of organic compounds widely used in life and production, with small molecular weight, and are present in coatings, adhesives, paints and detergents. Commonly used organic solvents include styrene, perchloroethylene, trichloroethylene, ethylene glycol ether and triethanolamine. Organic solvents can dissolve some organic compounds that are insoluble in water (such as grease, wax, resin, rubber, dye, etc.). They are characterized by being liquid at room temperature and pressure, having high volatility, and the properties of the solute and solvent remain unchanged during the dissolution process.

7. The method for preparing a highly safe semi-solid lithium-ion battery separator according to claim 2, characterized in that: In step 5, surfactants refer to any substance that can significantly reduce the surface tension of a liquid when added in small amounts. They are collectively referred to as surfactants. Their surface activity is for a specific liquid, usually water. One end of the surfactant is a non-polar hydrocarbon chain (hydrocarbon group), which has very little affinity with water and is often called a hydrophobic group; the other end is a polar group (such as -OH, -COOH, -NH2, -SO3H, etc.), which has a great affinity with water and is therefore called a hydrophilic group.

Citation Information

Patent Citations

  • Preparation method of doped graphene-polyethylene glycol-based polymer conversion film

    CN114944537A